GROUNDWATER VULNERABILITY ASSESSMENT TO SEAWATER INTRUSION THROUGH GIS - BASED GALDIT METHOD. CASE STUDY: ATALANTI COASTAL AQUIFER, CENTRAL GREECE - Lappas, I.; Kallioras, A.; Pliakas, F.; Rondogianni, Th. (Bulletin of the Geological Society of Greece, 2016)
Groundwater resources assessment has resulted in development of models that help identify the vulnerable zones. This paper presents a GIS-based hydrogeological index, named GALDIT, aiming at the assessment of aquifer vulnerability to seawater intrusion in Atalanti coastal aquifer, Central-Eastern Greece. The above acronym is formed from the most important factors controlling seawater intrusion, that is, four intrinsic hydrogeological parameters, one spatial parameter and one boundary parameter including Groundwater occurrence (aquifer type), Aquifer hydraulic conductivity, depth to groundwater Level above the sea (hydraulic head), Distance from the shore, Impact of seawater intrusion and aquifer’s Thickness. These factors nclude the basic requirements needed to assess the general salinization potential of each hydrogeological setting. Each parameter is evaluated with respect to the other to determine the relative importance of each factor. GALDIT model is described to assess and quantify the significance of vulnerability to seawater intrusion due to excessive groundwater withdrawals. Different thematic maps are prepared for seawater intrusion indicators and overlaid to develop the final vulnerability map. The derived map can be used as a tool for coastal groundwater resources management and areas’ determination of potential saltwater intrusion since the result of GALDIT ndex is classified based on vulnerability rate.